2006
DOI: 10.1542/peds.2005-1655
|View full text |Cite
|
Sign up to set email alerts
|

Therapy With Gastric Acidity Inhibitors Increases the Risk of Acute Gastroenteritis and Community-Acquired Pneumonia in Children

Abstract: This is the first prospective study performed in pediatric patients showing that the use of GA inhibitors was associated with an increased risk of acute gastroenteritis and community-acquired pneumonia in GERD-affected children. It could be interesting to underline that we observed an increased incidence of intestinal and respiratory infection in otherwise healthy children taking GA inhibitors for GERD treatment. On the contrary, the majority of the previous data showed that the patients most at risk for pneum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
205
3
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(217 citation statements)
references
References 14 publications
6
205
3
3
Order By: Relevance
“…Furthermore, longterm PPIs therapy (>2.5 years) has been associated with reduced bone mineralization, induced moderate hypergastrinemia and the development of enterochromaffin-like (ECL) cell hyperplasia in up to 50% of children [69]. Lastly, acid suppression itself is a recognized risk factor for communityacquired pneumonia, gastroenteritis, candidemia and necrotizing enterocolitis in preterm infants [70][71][72][73][74][75]. In addition, antacid drugs should not be considered in the management of infant GERD, as some absorbable components may induce side effects following chronic use (milk-alkali syndrome, aluminum toxicity, renal failure and hypercalcemia) [76][77][78].…”
Section: Pharmacological Gerd Management In Infants/young Childrenmentioning
confidence: 99%
“…Furthermore, longterm PPIs therapy (>2.5 years) has been associated with reduced bone mineralization, induced moderate hypergastrinemia and the development of enterochromaffin-like (ECL) cell hyperplasia in up to 50% of children [69]. Lastly, acid suppression itself is a recognized risk factor for communityacquired pneumonia, gastroenteritis, candidemia and necrotizing enterocolitis in preterm infants [70][71][72][73][74][75]. In addition, antacid drugs should not be considered in the management of infant GERD, as some absorbable components may induce side effects following chronic use (milk-alkali syndrome, aluminum toxicity, renal failure and hypercalcemia) [76][77][78].…”
Section: Pharmacological Gerd Management In Infants/young Childrenmentioning
confidence: 99%
“…Safety studies have shown that chronic acid suppression from PPIs may lead to increased risk of acute gastroenteritis, community-acquired pneumonia, Clostridium difficile infection and hip fracture [9][10][11]. These have been reported in older patients who may, similarly to infants, be immune compromised.…”
Section: Perspectivementioning
confidence: 99%
“…These have been reported in older patients who may, similarly to infants, be immune compromised. It is speculated that a decrease in gastric acid with PPIs may make these patients prone to infections or decreased absorption of calcium [9][10][11]. Orenstein's study showed that lansoprazole treatment in infants with GERD increased the risk of lower respiratory infections compared with placebo [3].…”
Section: Perspectivementioning
confidence: 99%
“…Although, early reports were very good and enthusiastic about this new drug in its use to children should not overestimate or underestimate. This is a drug which has its own side effects as reported [6,7] which can give gastrointestinal infections, bone fractures, hypomagnesaemia or excessive, and an increase in acidity (rebound) after treatment ends. Many scholars in the years before the release date of this drug rejected surgical treatment of reflux itself, saying that treatment with this preparation would be the final solution to the problem of reflux.…”
Section: Introductionmentioning
confidence: 99%